Phosphorus removal and N2O production in anaerobic/anoxic denitrifying phosphorus removal process: Long-term impact of influent phosphorus concentration. (March 2015) - Wang, Zhen; Meng, Yuan; Fan, Ting; Du, Yuneng; Tang, Jie; Fan, Shisuo
Highlights: Influent P concentration affected denitrifying dephosphatation and N2 O production. DPAOs was suppressed as influent P concentration was more than 20 mg L −1 . N2 O production was inhibited with the suppression of DPAOs. A modified feeding decreased effluent P concentration and N2 O production. Abstract: This study was conducted to investigate the long-term impact of influent phosphorus concentration on denitrifying phosphorus removal and N2 O production during denitrifying phosphorous removal process. The results showed that, denitrifying phosphate accumulating organisms (DPAOs) could become dominant populations quickly in anaerobic/anoxic SBR by providing optimum cultivating conditions, and the reactor performed well for denitrifying phosphorus removal. The influent phosphorus concentration significantly affected anaerobic poly- β -hydroxyalkanoates (PHA) synthesis, denitrifying phosphorus removal, and N2 O production during the denitrifying phosphorus removal process. As the influent phosphorus concentration was more than 20 mg L −1, the activity of DPAOs began to be inhibited due to the transformation of the available carbon source type. Meanwhile, N2 O production was inhibited with the mitigation of anoxic NO2 − -N accumulation. Adoption of a modified feeding could enhance denitrifying phosphorus removal and inhibit N2 O production during denitrifying phosphorous removal processes.